USULAN PENERAPAN METODOLOGI DMAIC DAN SERVICE BLUEPRINT UNTUK PERBAIKAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN PT MUTU - Fino Wahyudi Abdul (Universitas Mercu Buana, 2015)
Abstract. Costumer satisfaction is really important, because the customer willcome back to use the service. Customer satisfaction is also related to the quality ofservice received by the customer of a company products or services. The problemof service quality in a test lab PT MUTU is situated upon a description ofcustomer satisfaction regarding the analysis period of completion and certificatesdelivery time are still below standard PT MUTU against laboratory testingservices and there is a waste of time waiting for customers. Service qualityimprovement methods to the analysis period of completion and the delivery time acertificate is the DMAIC and lean approach, where the results of the improvementseen in the sigma level obtained. The tools used SIPOC, pareto diagram, CTQ,logic tree, two proportion test, DOE, p-chart, minitab-16. In addition underdiscussion used of the service blueprint analysis to saw linkages the improvementof service quality using DMAIC with the service process, points of contact withcustomers and the evidence seen by the customer service.Keyword: Service Quality, Lean, DMAIC, Service Blueprint, Sigma Level